1985
DOI: 10.1002/etc.5620040508
|View full text |Cite
|
Sign up to set email alerts
|

Effects of application procedures and irrigation on degradation and movement of aldicarb residues in soil

Abstract: Aldicarb was applied to potato plants in two locations in Wisconsin to determine the effects of application procedures and irrigation on degradation and movement of aldicarb residues, plant uptake, insect control and crop yield. Two application procedures (3.36 kg. AI/ha applied in the furrows at planting and 2.24 kg AI/ha applied as a top‐dress application consisting of a surface‐applied band covered with soil at plant emergence) and two irrigation regimens (medium water use based on evapotranspiration and he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2

Year Published

1986
1986
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 6 publications
0
5
2
Order By: Relevance
“…The estimated degradation rates so estimated for the two plots correspond to half-lives of 0.9 and 1 .O months for the planting and emergence applications, respectively. The finding of essentially the same half-life for both planting and emergence at the Phelps site at first may seem inconsistent with other studies which indicate slower rates of degradation for applications at planting [8,10]. However, the planting application was made in June rather than the normal time of late April or May due to wet fields, so little difference would be expected in the two half-lives that were observed.…”
Section: Results Of the Field Studycontrasting
confidence: 62%
See 1 more Smart Citation
“…The estimated degradation rates so estimated for the two plots correspond to half-lives of 0.9 and 1 .O months for the planting and emergence applications, respectively. The finding of essentially the same half-life for both planting and emergence at the Phelps site at first may seem inconsistent with other studies which indicate slower rates of degradation for applications at planting [8,10]. However, the planting application was made in June rather than the normal time of late April or May due to wet fields, so little difference would be expected in the two half-lives that were observed.…”
Section: Results Of the Field Studycontrasting
confidence: 62%
“…The finding of essentially the same half-life for both planting and emergence at the Phelps site at first may seem inconsistent with other studies which indicate slower rates of degradation for applications at planting [8,10]. Concentrations of the residues in soil adjacent to, or immediately below, where the band was originally placed are likely to be higher than elsewhere in the field.…”
Section: Results Of the Field Studycontrasting
confidence: 60%
“…The relatively rapid drop in the residue amounts from the at-planting treatment for the first three sampling intervals, and the relatively stable residue levels during the same period for the emergence application, followed by a large drop in residue levels from both treatments during the last two sampling intervals, does not seem to be supportive of first-order kinetics. However, first-order kinetics cannot be ruled out, considering the effects of lateral dispersion, soil variability and problems associated with sampling granular pesticides (residues in samples collected within 30 d of application are often lower than residues in samples collected at a later time (Jones et al., manu-script in preparation) [1,2]). It should also be noted that the last sampling interval was considerably longer than the other sampling intervals.…”
Section: Residuesmentioning
confidence: 99%
“…Monitoring herbicide transport through soil to groundwater is complex and early attempts that focused on analyzing herbicides in soil cores as a function of depth had limited success. For example, Wyman et al (1985 and evaluated aldicarb transport through soil by collecting 48 soil cores, each 3.6 m long, four times during a growing season. They observed no aldicarb below 2.4 m over a three year period and so concluded that aldicarb had degraded and did not pose a threat to groundwater quality.…”
Section: Groundwater Leachingmentioning
confidence: 99%